LANGKAH LANGKAH GURU DALAM PEMBELAJARAN ANAK AUTIS DI SLB BINA ANAK BANGSA PONTIANAK - Palupi, Woro; Mering, Aloysius; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the steps the teacher in teaching children with autism in SLB Bina Anak Bangsa Pontianak. To achieve the goal of the research conducted by the descriptive method to one teacher of five children and used a qualitative approach. The results showed that in planning the teacher made RPPH (Daily Lesson Plan) teacher refers to the curriculum in 2013 and then adapted to the conditions, capabilities, and needs of children with autism who will be selected jointly by the principal. Teachers also prepare the class before implementing the learning activities ranging from chairs, tables, kids games, tools and instructional media. Implementation of the learning activities of teachers opening the event by congratulating the morning and follow the child, teachers make eye contact with the child and guide children who have difficulty in learning. Evaluation of learning provided as evaluation quarterly done every three months to see the child's development, evaluation of results is more geared to the child's behavior at the time to understand the material, the child's behavior to friends and school environment, the evaluation process of teachers do every day or when learning activities take place ie correcting or correcting the child's behavior. The research concluded that prior to implementing the learning activities teachers make RPPH and adapts to the child's condition, in the implementation of the teacher began by welcoming the arrival of a child and make eye contact and learning evaluation consists of the evaluation process, the evaluation results and a quarterly evaluation.Keywords: Step By Step Learning, Autistic Children